2016
DOI: 10.1111/exd.13005
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of erythroid differentiation regulator 1 (Erdr1) plays a critical role in psoriasis pathogenesis

Abstract: c.474G>A, was considered to be responsible for the milder phenotype in our patient.Our RT-PCR for c.474G>A detected three transcripts, including two out-of-frame transcripts and an in-frame transcript. The inframe transcript displayed expression level equivalent to that of normal protein.In conclusion, we found that c.474G>A synonymous mutation causes abnormal splicing, and the in-frame mutant transcript accounts for the mild phenotype in our patient. The results further expanded the mutation spectrum in NS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Moreover, T helper 1 cytokines in AA are implicated in the dysregulation of the hair follicle’s immune homeostasis [9]. Erdr1 is negatively regulated by IL-18 [16], an IFN-γ inducing molecule. Therefore, we proposed that Erdr1 downregulation might be involved in the inflammatory cascade in AA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, T helper 1 cytokines in AA are implicated in the dysregulation of the hair follicle’s immune homeostasis [9]. Erdr1 is negatively regulated by IL-18 [16], an IFN-γ inducing molecule. Therefore, we proposed that Erdr1 downregulation might be involved in the inflammatory cascade in AA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lee et al [15] have reported that patients with AA have abnormal serum IL-18 levels. In our previous study, we have observed negative correlations between IL-18 and erythroid differentiation regulator 1 (Erdr1) in human keratinocytes [16]. Recently, it has been reported that Erdr1 plays an important role in the inflammatory process via regulating the immune system in various cutaneous chronic inflammatory disorders, such as psoriasis and rosacea [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Because serum IL-18 concentration is linked to psoriasis severity (PASI), IL-18 might be considered as a possible biomarker of psoriasis [24]. In HaCaT cells, Erdr1 expression is also inversely correlated with IL-18 [59]. Kim et al compared Erdr1 expression in skin tissues from human psoriasis patients and healthy volunteers.…”
Section: Roles Of Erythroid Differentiation Regulator 1 (Erdr1) Onmentioning
confidence: 99%
“…Based on our previous finding that Erdr1 expression is negatively correlated with that of IL-18 [6], we investigated whether IL-18 expression in synovial tissue was decreased in the rErdr1-treated group. , with the exception of the negative control (normal) group.…”
Section: Erdr1 Suppresses Cell Migration Through Inhibition Of Erk1/2mentioning
confidence: 99%